BMC Cell Biology
BMC Cell Biology is an open access, peer-reviewed journal that considers articles on all aspects of the biology of cells, including organelles and cellular compartments, trafficking and turnover, signaling, motility, adhesion, cell division, differentiation and programmed cell death.    .